Fabrication and Characterization of TiO2/GO/ZnO Composites Coated Cotton Fabric for Improved Hydrophobic Property - Suchanan Suksri; Aeimbhu, Areeya (Science Essence Journal, 2024)
This research focused on the hydrophobic properties of improving the cotton fabric coated with TiO2/GO/ZnO composites (TNPsGZ composites) powder using the dip-dry-cure method. The Fourier-transform infrared spectroscopy (FT-IR) revealed that TNPsGZ composites contained peaks associated with titanium dioxide (TiO2), graphene oxide (GO), zinc oxide (ZnO) and polyvinylpyrrolidone (PVP). The optical microscopic photographs demonstrated the TNPsGZ composite layer on the surface of the cotton fabric. The Scanning Electron Microscope (SEM) images confirmed that the TNPsGZ composites were evenly distributed on the surface of the cotton fabric. FT-IR spectra of the coated-TNPsGZ cotton fabric revealed the presence of C=O bond, C-O bond, O-H bond, C1-O-C4 cellulose bond and C=O bond of PVP. The coated-TNPsGZ cotton fabric significantly outperforms the pristine cotton fabric in terms of hydrophobic properties. As the results of this research, the contact angle of the coated-TNPsGZ cotton fabric ranged from 70° to 85° while the pristine cotton fabric showed 0°.